Great Zimbabwe, DEM and orthophoto - Löwenborg, Daniel; Mtetwa, Ezekia (Uppsala University, 2016)
High resolution orthophoto and digital elevation model of the site Great Zimbabwe, created using photogrammetry. Also an oblique photograph taken at the same time. 3D visualisations avaiable at https://sketchfab.com/lowenborg
Keywords: History and Archaeology; Historia och arkeologi